Are Solidarity Purchasing Groups a Social Innovation? A Study Inspired by Social Forces - Maestripieri, Lara (PARTECIPAZIONE E CONFLITTO, 2018)
The Social Forces theory was proposed by Beckert (2010) to study the interconnecting dynamic interrelations between institutions, networks and cognitive frames that underlie economic phenomena. In the context of this article, this theoretical perspective was applied to study Solidarity Purchasing Groups as a social innovation and to assess their capacity to create a new process of social inclusion for their suppliers. Despite being the most relevant alternative food networks in Italy, Solidarity Purchasing groups are only partially able to fulfil the promise of social innovation (by increasing the participation of beneficiaries and challenging pre-existing socio-economic dynamics) through the establishment of an alternative supply-chain alongside the one proposed by mass retailers. The results were obtained from an empirical investigation of 35 solidarity purchasing groups (2015/2016, nationally based), under the frame of the EU-funded CRESSI project.